Propuesta de un manual de funciones, valuación de puestos por puntos y evaluación de desempeño para la empresa “hogar y más” de la ciudad de Loja - Intriago Ochoa, Zonia Paquita (2015)
After the preparation of this thesis, it is necessary to highlight the main findings result of thorough and painstaking work displayed throughout the investigation process, which may be summarized as follows: This thesis bears the general title: "PROPOSAL FOR A Function Manual, VALUATION OF POSITIONS FOR POINTS AND PERFORMANCE EVALUATION FOR" Home & More "Loja". The company "HOME AND MORE" is an organization that works on selling household goods and appliances within the city of Loja and despite their competence level of the town, has captured a wide acceptance of citizenship, which supports its sales and good way to serve the customer when it comes to buy the goods on display in the company stores. The company "HOME AND MORE" currently has 15 employees, which are distributed in different positions both managers, administrative and operational within the company, their participation is directly in the production process of the company, which has him served to garner a prominent place within the local and regional market. The methodology used during the development of this research is ummarized in the use of the following methods: scientific method, deductive method, inductive method, Analytical method, historical method. In addition it was necessary to resort to the use of the following techniques: Direct Observation, Interview and Survey. The general objective that inspired the development of this research was: Function Manual, Valuation Points and Positions for Performance Assessment Company "HOME AND MORE" city of Loja; which by the way that was completely fulfilled. From the results, it was evident that the company does not have structured mission and vision and strategic objectives. A company lacks an organizational structure with defined roles and job evaluation points for a revaluation of the charges and to pay a fair wage. The valuation of positions held by points by determining certain factors including education, experience, initiative, responsibility for equipment, liability per person, mental effort, physical effort and risk to those who were given a weight depending on grades with a total weight of 100%; so the next score, Manager 295, 235 Secretary, Accountant 245, Treasurer 275, 170 Accounting Assistant, Sales Manager 255, Grocer 165, Cashier-biller 180, Rack 140, Sales Executive 205 and 180. Driver was obtained Once applied formulas became known that the posts of "Home & More" that are necessary to perform the salary adjustment according to the graph are found below the straight line, indicating that the salary received now it is not consistent their responsibilities, functions, expertise and working conditions within the company whose post are Accountant, the Head of Sales, CFO, Secretary and Executive sales with a recovery factor of 1.89. After making the performance evaluation, it became clear that the staff working in the company Home & More, has a total weighted score of 81.36, the same that is part of the equivalence of excellent, allowing us to interpret that classification as a business strength and a guarantee of good performance in the development of all business areas